Genetic modulation of rare earth nanoparticle biotransformation shapes biological outcomes - Mingming Tian; Di Wu; Xiao Gou; Ruibin Li; Xiaowei Zhang (Nature Communications)
Abstract The biotransformation of nanoparticles plays a crucial role in determining their biological fate and responses. Although a few engineering strategies (e.g., surface functionalization and shape control) have been employed to regulate the fate of nanoparticles, the genetic control of nanoparticle biotransformation remains an unexplored avenue. Herein, we utilized a CRISPR-based genome-scale knockout approach to identify genes involved in the biotransformation of rare earth oxide (REO) nanoparticles. We found that the biotransformation of REOs in lysosomes could be genetically controlled via SMPD1. Specifically, suppression of SMPD1 inhibited the transformation of La2O3 into sea urchin-shaped structures, thereby protecting against lysosomal damage, proinflammatory cytokine release, pyroptosis and RE-induced pneumoconiosis. Overall, our study provides insight into how to control the biological fate of nanomaterials.